Resonance absorption of ultrasonic waves in a magnetic fluid - SKUMIEL, A.; ŁABOWSKI, M.; JÓZEFCZAK, A. (Archives of Acoustics, 1998)
An external magnetic field applied to a magnetic fluid gives rise to the appearance of spherical and chain-like clusters. The present work is based on an acoustic method permitting the determination of the presence and size of the clusters by resonance absorption of an ultrasonic wave in a magnetic fluid under the influence of a magnetic field. Measurements by applying the pulse method of the variations of the ultrasonic absorption coefficient Δα for three frequencies in a selected magnetic fluid versus the external magnetic field strength have been reported.